ANÁLISIS ESTRUCTURAL DEL GEN MITOCONDRIAL CITOCROMO B Y DE LA REGIÓN CONTROL DE CYNOMYS MEXICANUS Y SPERMOPHILUS SPILOSOMA (RODENTIA: SCIURIDAE) - Guevara-Chumacero, Luis Manuel; López-Wilchis, Ricardo; Pedroche, Francisco F.; Barriga-Sosa, Irene de los Angeles (Instituto de Ecología, A.C., 2006)
The nucleotide sequences of the cytochrome b gene and of the control region are described for Cynomys mexicanus and Spermophilus spilosoma. The cytochrome b gene was characterized by the presence of eight non-synonymous substitutions at the inter-generic level, presented mainly in the transmembrane zone (87%). The control region was characterized by the presence of the conserved blocks, ETAS1 and CSB1; by the absence of repetitive sequences and by the conserved blocks, ETAS2, CSB2 and CSB3. Most of the inter-generic variation (47.9%) was observed in the ETAS domain. The structure of the control region was similar to that of phylogenetic related species.